Animal-inclusive community-led total sanitation (A-CLTS) - IMA World Health (IMA World Health, 2024)
With the support of a generous philanthropic foundation, IMA World Health and its partners conducted an Animal-inclusive Community-led Total Sanitation (A-CLTS) project in Segou, Mali. The project piloted an innovative WASH model that integrated animal waste management into CLTS based on extensive formative research to tailor interventions to the realities of rural Malian households. With partners USCET, the One Health Center at the International Livestock Research Institute (ILRI), and leading academic research partners, IMA World Health implemented a community intervention trial and conducted a series of workshops with community members and other key stakeholders to identify A-CLTS behavior change strategies that community members felt they could adopt and that have been demonstrated to impact child and family health elsewhere. This model can be adapted to other contexts as its results are likely relevant to other settings.